Fenomena Perkenalan Melalui Platform Digital dan Tantangannya terhadap Perkawinan Katolik - Jesica Cindini br Sembiring; Ambrosius Robertus Ratu; Y. Wilson B. Lena Meo (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The phenomenon of introduction through social media has become very common in this digital era. Social media offers ease and efficiency in introducing individuals to others, allowing them to meet, interact, and build relationships in a different way than traditional methods. However, the introduction of a partner through social media also brings its own challenges, emotional manipulation, and limitations in understanding the partner in depth. In the context of Catholic marriage, this phenomenon poses a serious challenge to canonical law. Canon law strictly regulates marriage in order to remain faithful to the Church's teaching of lifelong union and openness to procreation. However, the introduction of a couple through social media can affect the validity of the agreement, psychological readiness, and understanding of the nature of marriage. The Church needs to meet these challenges with a new pastoral approach, including the development of specific guidelines for the companionship of couples who start relationships through social media. This approach includes strengthening more intensive and comprehensive pastoral mentoring, utilizing social media as a tool for education and counseling and reminding couples of the importance of transparency and honesty in relationships. Thus, the Church faces the challenge of ensuring the psychological readiness of both parties and helping couples to understand more deeply about the marital commitments they make and to maintain the values of the sacrament of marriage in an ever-evolving digital world.